BENTUK PENYAJIAN SILEK GALOMBANG DI NAGARI PAGARUYUNG KECAMATAN TANJUNG EMAS KABUPATEN TANAH DATAR - Raudatul Hayati; Herlinda Mansyur; Zora Iriani (FBS Universitas Negeri Padang, 2013)
Abstract This research was aimed at revealing and documenting the presentation of Silek Galombang in Nagari Pagaruyung Kecamatan Tanjung Emas Kabupaten Tanah Datar which was performed in welcoming the official guests. This was a qualitative research which used descriptive method. In collecting the data, the researcher observed the process of welcoming the guests in Istano Silinduang Bulan Pagaruyung. Silek Galombang is a kind of arts performances which applies self-defense (silat) arts movements performed by 8 men mastering silek and 2 men carrying carano. The performance was preceded by kata sambah and batagua accompanied by some musical instruments including calenang, gandang, bansi and sarunai. The costumes worn by anak silek were baju taluak balango, celana guntiang ampek hitam, deta batik hitam and sesampiang. The men bringing the carano wore black and blue taluak balango suit and red sesampiang. Silek Galombang was performed in a group with rampak simultan and straight-line floor pattern. This was done in a field which was closed by delivering batagua words and sowing beras kuning. Kata kunci : Silek Galombang, laki-laki, carano, kata sambah, bataguah